Neuron Type-Dependent Synaptic Activity in the Spinal Dorsal Horn of Opioid-Induced Hyperalgesia Mouse Model - Kearns, Austin; Jayasi, Jazmine; Liu, Xin; Wang, Jigong; Shi, Yuqiang; Chung, Jin Mo; La, Jun-Ho; Tang, Shao-Jun; Bae, Chilman (Frontiers in Synaptic Neuroscience, 2021)
Opioids are widely used for pain relief; however, chronic opioid use causes a paradoxical state of enhanced pain sensitivity, termed ‘Opioid-induced hyperalgesia (OIH)’. Despite the clinical importance of OIH, the detailed mechanism by which it enhances pain sensitivity remains unclear. In this study, we tested whether repeated morphine induces a neuronal circuit polarization in the mouse spinal dorsal horn. Transgenic mice expressing GFP to neurokinin-1 receptor for excitatory neurons (sNK1Rn) and GABAergic interneurons (sGABAn) that received morphine (20 mg/kg, once daily for 4 consecutive days (i.p.)) developed mechanical hypersensitivity. Repeated morphine altered synaptic strengths in the SDH as a specific cell-type but not in a gender-dependent manner. In sNK1Rn and non-tonic firing neurons, repeated morphine treatment significantly increased frequency of spontaneous excitatory postsynaptic current (sEPSC) and evoked EPSC (eEPSC). In addition, repeated morphine treatment significantly decreased evoked inhibitory postsynaptic current (eIPSC) in sNK1Rn. Conversely, in sGABAn and tonic firing neurons, repeated morphine treatment significantly decreased sEPSC frequency and eEPSC, but had no change of eIPSC in sGABAn. Interestingly, repeated morphine treatment significantly decreased neuronal rheobase of sNK1Rn but had no effect on sGABAn. These findings suggest that spinal neuronal circuit polarization maybe the mechanism of OIH and identify a potential therapeutic mechanism to prevent or treat opioid-induced pain.